UNPACKING THE DIFFERENTIAL IMPACT OF FAMILY PLANNING POLICIES IN CHINA: ANALYSIS OF PARITY PROGRESSION RATIOS FROM RETROSPECTIVE BIRTH HISTORY DATA, 1971–2005. Issue 6 (10th January 2018) - Qin, Min; Falkingham, Jane; Padmadas, Sabu S.
Summary: Although China's family planning programme is often referred to in the singular, most notably the One-Child policy, in reality there have been a number of different policies in place simultaneously, targeted at different sub-populations characterized by region and socioeconomic conditions. This study attempted to systematically assess the differential impact of China's family planning programmes over the past 40 years. The contribution of Parity Progression Ratios to fertility change among different sub-populations exposed to various family planning policies over time was assessed. Cross-sectional birth history data from six consecutive rounds of nationally representative population and family planning surveys from the early 1970s until the mid-2000s were used, covering all geographical regions of China. Four sub-populations exposed to differential family planning regimes were identified. The analyses provide compelling evidence of the influential role of family planning policies in reducing higher Parity Progression Ratios across different sub-populations, particularly in urban China where fertility dropped to replacement level even before the implementation of the One-Child policy. The prevailing socioeconomic conditions in turn have been instrumental in adapting and accelerating family planning policy responses to reducing fertility levels across China.